Statement by the Managing Director on the Independent Evaluation Office's Report on the IMF and the Crises in Greece, Ireland, and Portugal : An Evaluation by the Independent Evaluation Office. (Policy Papers; Policy Paper, 2016)
I welcome the report of the Independent Evaluation Office (IEO) on the Euro Area crisis programs. Their work provides an independent and in-depth account, which I have no doubt will make an important contribution to understanding the Fund's approach to the crisis. As I have emphasized repeatedly, the IEO plays a vital role in enhancing the learning culture within the Fund, strengthening the Fund's external credibility, and supporting the Executive Board's institutional governance and oversight responsibilities.